2007
DOI: 10.1097/jom.0b013e3180dca598
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Risk Factors of Early Respiratory Responses to Exposure to Cotton Dust in Newly Exposed Workers

Abstract: This study of workers naive to cotton dust exposure has demonstrated that respiratory symptoms and acute airway responses develop early following first exposure, and a tolerance effect develops in those workers with the continued exposure. Current smoking and increasing exposure predicts the development of work-related lower respiratory tract symptoms, while early symptoms and acute airway changes across the working week predict the longitudinal loss of lung function at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 16 publications
8
25
0
1
Order By: Relevance
“…The prevalence of persistent cough and phlegm in this study was very similar to that of other studies,9 11 17 although surprisingly there were no significant differences in the reporting of symptoms between current smokers, ex-smokers and non-smokers in our study. This finding contradicts the findings from previous studies which reported all respiratory symptoms except byssinosis to be significantly more frequent in smokers than non-smoking cotton workers 2 20.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of persistent cough and phlegm in this study was very similar to that of other studies,9 11 17 although surprisingly there were no significant differences in the reporting of symptoms between current smokers, ex-smokers and non-smokers in our study. This finding contradicts the findings from previous studies which reported all respiratory symptoms except byssinosis to be significantly more frequent in smokers than non-smoking cotton workers 2 20.…”
Section: Discussionsupporting
confidence: 90%
“…Intriguingly, endotoxin was not associated with any of the respiratory symptoms and, when included in the multivariate model, did not have any independent predictive effect. These findings corroborate the earlier findings from the cross-sectional study in cotton workers in Turkey,9 but contradict those of a German textile mill that reported a fourfold increased risk of cough in individuals exposed to high endotoxin concentrations, compared to those exposed to low levels of endotoxin 23. The range of endotoxin exposure in the Chinese and German studies was 25–7590 EU/m 3 and 9–7177 EU/m 3 , respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another studies revealed significantly decreased mean FEV 1 and FVC in cotton workers which are in accordance with result of the present the study (Vyas, 2012;Bakirci et al, 2007). A study in Egypt showed a significant decline in FEF 25-75% in exposed subjects compared to non-exposed subjects (Khalifa et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…Chronic exposure can provoke different symptoms, such as fever, headache, throat irritation, cough, wheezing and thoracic oppression. 26 There are several studies that demonstrate that exposure to endotoxins cause a fall in FVC and in FEV 1 ; nonetheless, these were done in work settings, with intense occupational exposure. Contrarily, other studies show that exposure to endotoxins at early ages seems to have a protector effect against the development of atopic diseases by means of a stimulus of the Th-1 response versus Th-2.…”
Section: Biological Contaminationmentioning
confidence: 98%